A bioinspired capillary-driven pump for solar vapor generation. (December 2017) - Liu, Huidong; Zhang, Xiantao; Hong, Zixin; Pu, Zhigang; Yao, Qingyu; Shi, Jincheng; Yang, Guobiao; Mi, Bowen; Yang, Bing; Liu, Xiang; Jiang, Haifeng; Hu, Xuejiao
Abstract: Harvesting solar energy for vapor generation has attracted large amount of attention due to its promise for applications in water purification, desalination, power generation, and so on. Many structures based on the two-layered design or the plasmonic enhanced evaporation have been reported to promote the efficiency of solar vapor generation. Inspired by the transpiration phenomenon in plant, we report that a capillary-driven pump can be used for highly efficient solar vapor generation. The pump is mainly consisted of a porous hydrophilic modified NiO (M-NiO) disc and a one-dimension water supply channel. The M-NiO with a three-layered structured TiAlON-based nanocomposite absorber deposited on its surface can efficiently capture solar radiation (absorptance of 0.97). Driven by the capillary force in the porous M-NiO, the pump can continuously wick water via the one-dimension channel to the solar absorber for evaporation, achieving solar-to-vapor efficiency of 73% at 1 sun and 90% at 4 suns. The high conversion efficiency can be attributed to the high absorption ability of the M-NiO disc and the one-dimension water supply design to limit the thermal loss. This new design with advantage of easy scale-up provides an efficient approach to harvest sunlight for solar vapor generation in low solar concentrations. Graphical abstract: Highlights: Nanocomposite absorber was deposited on porous NiO with absorptance of 0.97. Capillary-driven pump with 1-D water path was designed for solar vapor generation. The pump exhibited solar thermal efficiency of 73% at 1 sun and 90% at 4 suns.